A framework for context-aware application programming on smart phone. (2018) - Sung, Baek Gyoon
Our framework can be classified in six main groups. Sensor manager retrieves and updates a program component that collects sensor data from the library. Data generator generates current or statistic summary data, or statistic index. Context generator is for developing a program to generate automatically various data and context from existing program skeletons. Class library and API is for developing a service application program or a program to extract and infer various data and context. Service generator generates a program component for summary reports, inference chain reports, communication services and personalised services. Inference engine infers context by rule-based and case-based reasoning. The developed application by our framework is extracted and infers various context such as 'moving' or 'stay home' and offers users the personalised services about current user's context.